A novel lipids recovery strategy for biofuels generation on microalgae Chlorella cultivation with waste molasses. (December 2020) - Yew, Guo Yong; Khoo, Kuan Shiong; Chia, Wen Yi; Ho, Yeek-Chia; Law, Chung Lim; Leong, Hui Yi; Show, Pau Loke
Graphical abstract: Highlights: Microalgae cultivation with waste molasses shown reduction on COD, TSS and nitrate. Lipid recovery up to 92.84 % of recovery and 8.3 folds for the enhancement value. The system has shown potential of removal of Sulphur content at the biomass. A potential disruptive-extraction method for direct conversion of lipids into FAME. Abstract: This study demonstrated a novel approach of lipids extraction with simultaneous biofuels conversion on microalgae Chlorella sorokiniana CY-1 cultivation using waste molasses as culture medium. The lipid extraction process was based on a hybrid liquid biphasic system (HLBS) which comprises of disruptive and extractive solvents in a single system. The microalgae cultivation with waste molasses showed a reduction in the chemical oxygen demand (COD), total suspended solid (TSS) and nitrate content on the waste medium (61.48 %, 63.94 % and 63.79 %, respectively). Additionally, a prompt lipids extraction with a recovery of 92.84 % and a cell disruption enhancement of 8.3-fold in the organic solvent phase was attained. The acid-treated C. sorokiniana CY-1 biomass showed a composition of carbon at 61.3 %, oxygen at 33.2 %, nitrogen at 5.5 % and potassium at 0.12 %. Sulphur content was not detected in the microalgae biomass and this had aided the production of fatty acids methyl ester (FAME) which was observed by a gas chromatographic-flame ionisation detector (GC-FID) profile. A disruptive-extraction method using acid assisted phase on HLBS showed potential for direct conversion of lipids into FAME to produce biofuels for engine combustion.